Application of ANN in Milling Process: A Review. (26th April 2011) - Al-Zubaidi Al-Zubaidi, Salah Salah; Ghani Ghani, Jaharah A. Jaharah A.; Che Haron Che Haron, Che Hassan Che Hassan
Abstract : In recent years the trends were towards modeling of machining using artificial intelligence. ANN is considered one of the important methods of artificial intelligence in the modeling of nonlinear problems like machining processes. Artificial neural networks show good capability in prediction and optimization of machining processes compared with traditional methods. In view of the importance of artificial neural networks in machining, this paper is an attempt to review the previous studies and investigations on the application of artificial neural networks in the milling process for the last decade.